Atypical Teratoid/Rhabdoid Tumor of the Central Nervous System in Children: Case Reports and Literature Review - Guo, Gengyin; Zhuang, Jianfeng; Zhang, Keke; Zhou, Zhizhen; Wang, Yanjun; Zhang, Zhen (Frontiers in Surgery, 2022)
Atypical teratoid/rhabdoid tumor of the central nervous system is a highly malignant tumor that mainly occurs in children under the age of three years and has only been rarely described in adults. The fact that AT/RT patients have such a terrible prognosis is even more regrettable. Herein, we reported two special cases of AT/RT, both of which were under three years old. Symptoms at presentation included increased intracranial pressure and cerebellar symptoms, such as headache, altered gait, and ataxia. As for the tumor location, one was infratentorial in the posterior fossa, and the other was the right lateral ventricle. Preoperative magnetic resonance imaging scans showed calcification, and heterogeneous contrast enhancement in the lesions. The mass was excised surgically for the progression of symptoms. Postoperative pathologies of the tumors combined with immunohistochemistry revealed AT/RT. AT/RTs are often misdiagnosed as other types of brain tumors due to the lack of specific radiological features and other key characteristics. To improve awareness of AT/RT on the differential diagnosis of intracranial lesions among clinicians, we present this report and briefly summarize previous cases.